English competency for employment: Actualizing industry needs with the proficiency in enterprise communication - Zubairi, Ainol Madziah; Sarudin, Isarji; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari (Prestariang Systems Sdn Bhd, 2012)
This white paper on the industry's need for graduates with English language competency was published by Prestariang Systems Sdn Bhd following a market survey with 14 industries in Malaysia.